Vocal Cues to Male Physical Formidability - Mailhos, Alvaro; Egea-Caparrós, Damián Amaro; Guerrero Rodríguez, Cristina; Luzardo, Mario; Kiskimska, Nansi Dilyanova; Martínez Sánchez, Francisco (Frontiers in Psychology, 2022)
Animal vocalizations convey important information about the emitter, including sex, age, biological quality, and emotional state. Early on, Darwin proposed that sex differences in auditory signals and vocalizations were driven by sexual selection mechanisms. In humans, studies on the association between male voice attributes and physical formidability have thus far reported mixed results. Hence, with a view to furthering our understanding of the role of human voice in advertising physical formidability, we sought to identify acoustic attributes of male voices associated with physical formidability proxies. Mean fundamental frequency (F0), formant dispersion (Df), formant position (Pf), and vocal tract length (VTL) data from a sample of 101 male voices was analyzed for potential associations with height, weight, and maximal handgrip strength (HGS). F0 correlated negatively with HGS; Pf showed negative correlations with HGS, height and weight, whereas VTL positively correlated with HGS, height and weight. All zero-order correlations remained significant after controlling for false discovery rate (FDR) with the Benjamini–Hochberg method. After controlling for height and weight—and controlling for FDR—the correlation between F0 and HGS remained significant. In addition, to evaluate the ability of human male voices to advertise physical formidability to potential mates, 151 heterosexual female participants rated the voices of the 10 strongest and the 10 weakest males from the original sample for perceived physical strength, and given that physical strength is a desirable attribute in male partners, perceived attractiveness. Generalized linear mixed model analyses—which allow for generalization of inferences to other samples of both raters and targets—failed to support a significant association of perceived strength or attractiveness from voices alone and actual physical strength. These results add to the growing body of work on the role of human voices in conveying relevant biological information.